Comparison Study of Urinary Retention Incidence in Assisted Vaginal Delivery Case with and without 24-Hour Catheterization - Eighty Mardiyan Kurniawati1, Hari Parathon2, Suskhan Djusad1, Fernandy Moegni1, Junizaf1, Budi Iman (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Urinary retention is a condition commonly seen after vaginal delivery, especially in the highrisk cases, such as assisted vaginal delivery, grade 3-4th perineal rupture, or another high risk. Urinary retention caused by unsynchronized between the contraction of the bladder detrusor. Urinary catheterization is one of the preventions of urinary retention. It gives a time for perineal trauma to relieve and no longer edema, so that urethra can be fully relaxed. Therefore, 24-hour catheterization expected to prevent bladder overdistention. It also prevents the bladder from becoming atonia. Objective: This research aims to study the incidence of urinary retention in assisted vaginal delivery with and without 24-hour catheterization. Method: This study used randomized control trials that compared two groups with 24-hour catheterization and without 24-hour catheterization. This study was conducted on 40 women in each group who experienced assisted vaginal birth at Dr Soetomo Hospital, Indonesia. Result: Six women (15%) experienced urinary retention with 24-hour catheterization and six women (15%) had urinary retention without catheterization. There was no significant difference in the incidence of urinary retention with 24-hour catheterization and without 24-hour catheterization (p-value = 1.00). Also, there was no significant interference of urinary retention in the normal and prolonged second stage of labor (p-value = 0.736), and there was no significant risk factor contributing to urinary retention. Conclusion: No significant difference in urinary retention occurred in assisted vaginal delivery with and without 24-hour catheterization